2013
DOI: 10.1159/000354197
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Expansion of Traumatic Choroidal Rupture with Delayed-Developed Outer Retinal Changes

Abstract: Background: This study aims to report the expansion of a choroidal rupture site caused by blunt ocular trauma using scanning laser ophthalmoscope-optical coherence tomography. Case Report: The clinical course of a 15-year-old girl with a traumatic ocular injury after being hit in the eye by an elbow was evaluated. Upon the first examination, the best-corrected visual acuity was 16/20. The findings were subretinal pigment epithelial hemorrhage and vertical choroidal rupture. Three weeks after the trauma, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…6 Furthermore, it would be hard to decide the appropriate line for the OCT B-scan examination when the typical fundus findings were unclear. 1,3,7,8 When compared with the findings on en-face OCT images, we observed the OCT B-scan images at the exact location of the lesions. Therefore, when assessing fine lesions by OCT B-scan images, a comparison with en-face OCT images seems useful.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…6 Furthermore, it would be hard to decide the appropriate line for the OCT B-scan examination when the typical fundus findings were unclear. 1,3,7,8 When compared with the findings on en-face OCT images, we observed the OCT B-scan images at the exact location of the lesions. Therefore, when assessing fine lesions by OCT B-scan images, a comparison with en-face OCT images seems useful.…”
Section: Discussionmentioning
confidence: 87%
“…In a case of a choroidal rupture, secondary choroidal neovascularization that occurred at a relatively early stage was reported. 7 Therefore, frequent follow-up evaluations are optimal. In the current case, we easily followed the morphologic changes associated with the choroidal rupture using en-face OCT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is interesting because we expected the development of macular edema. Patients with mild cases of commotio retina present transient visual loss and recover spontaneously, but more severe cases may be associated with permanent visual loss [10,15]. The decrease in CMT in severe cases may be associated with the cellular loss and may be associated with a worse prognosis that should be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…It may be restricted to the macula or involve areas of the peripheral retina [13]. Previously, macular findings after trauma were described as ranging from mild pallor to macular hole formation [14,15]. Based on histopathological findings from the eyes of human cadavers, investigators showed that the major site of injury in commotio retinae is likely at the photoreceptor outer segmented-retinal pigmented epithelial junction [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation